1994
DOI: 10.1159/000126778
|View full text |Cite
|
Sign up to set email alerts
|

Increased Numbers of Corticotropin-Releasing Hormone Expressing Neurons in the Hypothalamic Paraventricular Nucleus of Depressed Patients

Abstract: The hypothalamo-pituitary-adrenal (HPA) axis is known to be activated in depressed patients. Although direct evidence is lacking, this activation is hypothesized to be due to hyperactivity of corticotropin-releasing hormone (CRH) neurons of the hypothalamic paraventricular nucleus (PVN). Recent immunocytochemical studies in experimental animals and in humans showed that the number of CRH-expressing neurons correlated with the activity of these neurons. In addition, colocalization of AVP in CRH neurons has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
299
3
12

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 613 publications
(334 citation statements)
references
References 50 publications
14
299
3
12
Order By: Relevance
“…It has been revealed that CRH mRNA level is increased in PVN after chronic mild stress [13] . Our finding is consistent with the previous reports that demonstrate hyperactivation of CRH neurons in PVN both in stressed rats [13] and in the brain of depressive patients [3,4] . Besides, we have found in the same model that CRH mRNA expression is increased after CUMS [27] .…”
supporting
confidence: 94%
See 1 more Smart Citation
“…It has been revealed that CRH mRNA level is increased in PVN after chronic mild stress [13] . Our finding is consistent with the previous reports that demonstrate hyperactivation of CRH neurons in PVN both in stressed rats [13] and in the brain of depressive patients [3,4] . Besides, we have found in the same model that CRH mRNA expression is increased after CUMS [27] .…”
supporting
confidence: 94%
“…Patients with depression exhibit elevated CRH mRNA and peptide levels [3,4] , suggesting that the hyperactivity of CRH-containing neurons is associated with, or contributes to the pathophysiology of depression. This idea is reinforced by the following observations: (1) CRH level is increased in cerebral spinal fluid of depressed patients [5] ; (2) Antidepressant drugs can decrease HPA-axis activity [6] ; (3) CRH injection into the brain of laboratory animals induces signs and symptoms of major depression, and the same syndromes are observed in transgenic mice in which CRH is over-produced [7] ; (4) The finding that single-nucleotide polymorphisms (SNPs) in CRH receptor1 gene (CRHR1) are associated with increased susceptibility to major depression [8] is an argument for the direct involvement of CRH in the symptomatology of depression. The behavioral response to stress is associated with CRH changes in the central nervous system (CNS) [9] .…”
Section: Introductionmentioning
confidence: 99%
“…The evidence for the specificity, and clinical and biological plausibility of endophenotypes related to dysfunctions of the hypothalamic and extrahypothalamic CRH system for MDD is abundant: Levels of CRH in the CSF are elevated in some depressed subjects (Nemeroff et al, 1984), while the pituitary response to CRH appears appropriate given the high cortisol levels (Gold et al, 1986); the number of CRHsecreting neurons in limbic brain regions is increased (Raadsheer et al, 1994); the number of CRH binding sites in the frontal cortex is reduced, possibly as a compensatory response to increased CRH concentrations (Nemeroff et al, 1988); CRH produces a number of physiological and behavioral alterations that resemble the symptoms of major depression including decreased appetite, disrupted sleep, decreased libido, and psychomotor alterations (Nemeroff, 1996); and anxiety and depression scores have been reduced following CRH-1 receptor blockade (Zobel et al, 2000).…”
Section: Hpa Axis and Crhmentioning
confidence: 99%
“…Clinical studies have also addressed the hypothesis that AVP is associated with depressive state. Raadsheer et al (1994) showed that the PVN of depressed patients contains 4 times the number of CRH expressing cells and 3 times the number of CRH neurons that coexpressed AVP as compared to normal controls. Similarly, the number of AVP-ir neurons is increased in the PVN of depressed patients (Purba et al, 1996).…”
Section: Hpa Alterations In Clinical Disordersmentioning
confidence: 99%